COMPARISON OF DISCOVERY LEARNING TEACHING MODEL AND STUDENT TEAM ACHIEVEMENT DIVISION (STAD) ON COGNITIVE ACHIEVEMENT ABOUT SCIENCE OF BUILDING THE TENTH YEAR STUDENTS SMK NEGERI 1 KENDAL - Fajar Purnandita; Agus Efendi; Budi Siswanto (Indonesian Journal Of Civil Engineering Education, 2016)
width: 0px; "> </The goals of this research to examines the differences, to examines the influences and to determine the effectiveness of the using of Discovery Learning Teaching Model and Student Team Achievement Division (STAD) in increasing students’ cognitive achievement. This research includes to comparative/experimental research. The research populations are the tenth year students TGB of SMK Negeri1 Kendal. There were 54 students divided into two groups, each of them consist of 27 students, they are the TGB A group and the TGB B group that use. The techniques of collecting data are test, observation and documentation. Instruments of validity use validity test, reliability test, level of difficulty and distinctive. The analyzing of pretest with normality test that uses Shapiro-Wilk Test, balancing test uses T test, the homogeneity test uses F test. The technique of the analyzing data uses hypothesis test with ANOVA using SPSS. The result showed that: 1) There were difference about learning achievement using of Discovery Learning teaching model and Student Team Achievement Division (STAD) (Fscore(9.415)›Ftable(4,03) and Sig. (0.003)‹ α(0.005)), 2) There were difference using of Discovery Learning teaching model and Student Team Achievement Division (STAD) to wards students cognitive achievement (Sig. (0.00) ‹ α (0.005) and F(0.05,1,104) (14,386) › Ftable (3.93)), 3) STAD teaching model were more effective in increasing students cognitive achievement that can be seen from the average score of students cognitive achievement about science of building (Mean STAD = 60.59 › Mean DL = 54.20). .Keywords: Teaching Model